(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To investigate certain related factors and clinical characteristics of infantile hemangioma in patients at the National Hospital of Dermatology and Venereology from July 2024 to July 2025. Subjects and methods: A cross-sectional descriptive study was conducted on 141 infants with hemangiomas visited and treated at the National Hospital of Dermatology and Venereology from July 2024 to July 2025. Results: Among the 141 patients surveyed, the average age at the time of examination was 0.51 years. There were 52 male patients (36.88%) and 89 female patients (63.12%). Of these, 130 children (92.2%) had the superficial type, while 11 children (7.8%) had the mixed type. The average birth weight was 3062 grams, and the average maternal age was 28.92 years, only 5 patients (3.55%) had a first-degree family history of hemangioma. Most of the patients were first-born children (61.11%); second-born (30.56%), and third-born (8.33%). Hemangioma lesions were most commonly found on the head and neck, accounting for 43.97%, they were less frequently found on the trunk (23.4%), on the upper limbs (19.86%), and least common on the lower limbs (12.77%). Three patients (2.13%) had a relevant obstetric history, and complications of ulceration or bleeding were recorded in three patients (2.13%). Conclusion: Infantile hemangioma is a common benign lesion in females, with little association between hemangiomas and risk factors such as advanced maternal age, low birth weight, family history, or obstetric history. Lesions were most commonly found in the head and neck region and least commonly on the lower limbs.